2015
DOI: 10.1590/s1516-8913201500372
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of ethanol production from deproteinized whey by Kluyveromyces marxianus: An analysis about buffering capacity,thermal and nitrogen tolerance

Abstract: The production of value-added products could be a valuable option for cheese wastewater management. However, this kind of study cannot just focus alone on getting the final product. This also necessitates studies on the dynamics of bioprocesses. With these as background, the present investigation aimed at evaluating the buffering capacity of deproteinized whey and effect of temperature and nitrogen source on ethanol yields from it. The batch fermentation conditions used to evaluate ethanol production were temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…It is obvious that the fermentation medium containing pure lactose or inulin as the carbon source provides a much higher biomass productivity (Q x ) and yield (Y x/s ) per unit of the substrate consumed. This could be explained by differences in the substrate composition, for instance, by the presence of osmolytes in the whey permeate as mentioned above [41] and perhaps even more by a possible nitrogen deficiency in this source unlike the pure lactose-and inulin-containing media containing the yeast extract supplement [42]. At the same time the differences in the volumetric ethanol productivity (Q p ) and the specific rate of product formation (qp) for the whey permeate medium are relatively less pronounced when compared with the other two media (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…It is obvious that the fermentation medium containing pure lactose or inulin as the carbon source provides a much higher biomass productivity (Q x ) and yield (Y x/s ) per unit of the substrate consumed. This could be explained by differences in the substrate composition, for instance, by the presence of osmolytes in the whey permeate as mentioned above [41] and perhaps even more by a possible nitrogen deficiency in this source unlike the pure lactose-and inulin-containing media containing the yeast extract supplement [42]. At the same time the differences in the volumetric ethanol productivity (Q p ) and the specific rate of product formation (qp) for the whey permeate medium are relatively less pronounced when compared with the other two media (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it can be concluded that there was no influence of particle-network strength (via specific energy of cohesion) between the enzyme and liquid phases, nor did the viscoelastic state of the fermented medium negatively interfere with enzyme separation (Dandouh et al, 2016). Moreover, the final lactose content observed in batch fermentation is likely to result in a decrease of chemical oxygen demand, which indicates the amount of oxygen required to oxidize an organic compound to carbon dioxide (Colognese et al, 2015;Moreira et al, 2015). Figure 3 shows the evolution of fresh biomass and pH under optimal conditions (5%-deproteinized CWP solution).…”
Section: Resultsmentioning
confidence: 99%
“…The production kinetics of microorganisms was measured in Erlenmeyer flasks using the optimum conditions for the production of β-galactosidase. Aliquots were removed every 24 h (Colognese et al, 2015;Moreira et al, 2015).…”
Section: Media and Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this seems very promising, the high cost of this type of fuel is a limiting factor in commercial use. Intensive scientific studies are needed to find a highly productive process by using inexpensive and renewable substrates, including food industry by-products such as corn steep liquor (CSL) and cheese whey (CW) (AMORIM et al, 2011;CHOI et al, 2010;DODIĆ et al, 2009;LEITE et al, 2008;MOREIRA et al, 2015).…”
Section: Introductionmentioning
confidence: 99%